Educação patrimonial em paleontologia na região central do RS: construindo uma cartilha para alunos do ensino médio - Stochero, Cleusa Maria Pasetto (2018)
The present study deals with Heritage Education as a recognizing element of the Palaeontological Heritage of the central region of Rio Grande do Sul State. Being intrinsically linked to diverse activities of everyday life in society, and yet being little known and little valued, it becomes essential the diffusion of the Palaeontological Heritage. Knowledge of heritage leads to a process of appreciation and appropriation by society, and the school, because it is a space to accompany the formation of individuals, therefore, it has a determining role in preservation practices. Patrimonial Education is a multidisciplinary proposal directed to the knowledge of cultural heritage and, in this case, specifically the Paleontological Heritage. Thus, in order to clarify the community and making it understand the importance of preserving the fossils and the regional paleontological sites, it is intended to elaborate, for the students of the high school, the educational booklet entitled "Paleontology of the central region of Rio Grande do Sul: understand and preserve it". The construction of this educational tool aims to inform students about the fossiliferous heritage of the region. For its elaboration, basic concepts will be used in simple language and of easy understanding. This approach makes the material attractive, clear and accessible.